A Rare Collection of Artifacts, Including Terracottas, Photographic Plates, and Prints from the Collection of Archaeologist Paul Gaudin - Jean-Sylvain Caillou (Les Carnets de l’ACoSt)
On Wednesday, June 1, 2022, a rare collection of ancient objects, including terracottas, photographic plates, and prints from the collection of archaeologist Paul Gaudin were put up for sale by the auction house Rouillac in the Château d'Artigny, Montbazon, France.